Decrypting the cellular and molecular intricacies associated with COVID-19-induced chronic pain - Rani M.; Uniyal A.; Akhilesh; Tiwari V. (My University, 2025)
Pain is one of the clinical manifestations that can vary from mild to severe symptoms in COVID-19 patients. Pain symptoms can be initiated by direct viral damage to the tissue or by indirect tissue injury followed by nociceptor sensitization. The most common types of pain that are reported to occur in COVID-19 patients are headache, myalgia, and chest pain. With more and more cases coming in the hospitals, many new and unique symptoms of pain are being reported. Testicular and abdominal pain are rare cases of pain that are also being reported and are associated with COVID-19. The SARS-CoV-2 virus has a high affinity for angiotensin-converting enzyme-2 receptor (ACE-2) which acts as an entry point for the virus. ACE-2/ Ang II/AT 1 receptor also participates directly in the transmission of pain signals from the dorsal horn of the spinal cord. It induces a series of complicated responses in the human body. Among which the cytokinetic storm and hypercoagulation are the most prominent pathways that mediate the sensitization of sensory neurons facilitating pain. The elevated immune response is also responsible for the activation of inflammatory lipid mediators such as COX-1 and COX-2 enzymes for the synthesis of prostaglandins (PGs). PG molecules especially PGE2 and PGD2 are involved in the pain transmission and are found to be elevated in COVID-19 patients. Though arachidonic acid pathway is one of the lesser discussed topics in COVID-19 pathophysiology, still it can be useful for explaining the unique and rarer symptoms of pain seen in COVID-19 patients. Understanding different pain pathways is very crucial for the management of pain and can help healthcare systems to end the current pandemic situation. We herein review the role of various molecules involved in the pain pathology of COVID-19. © 2022, The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature.